Adolescentes com COVID-19: associação dos determinantes sociais de saúde com a qualidade de vida - Mesquita, Kirley Kethellen Batista (2023)
The COVID-19 pandemic interferes with different dimensions of adolescents' lives, both in physical and psychosocial aspects, and may be associated with an increase in adverse health effects in the long term. Thus, the assessment of quality of life taking into account the influence of social determinants of health makes it possible to assess individual aspects of adolescents and motor and social dynamics. In this perspective, this study aimed to evaluate the quality of life of adolescents who had COVID-19 in Ceará. This is an ecological study, with a cross sectional design, developed in the State of Ceará. The sample consisted of 235 adolescents, who met the inclusion criteria: being aged between 10 and 19 years; having a diagnosis of COVID 19 confirmed by laboratory test; having been notified in e-SUS-Notifica; smartphone-type cell phone and be able to access the internet. The instruments used in data collection were: Adolescent characterization form and the Quality of Life Questionnaire (SF-36). For data collection, a message was sent via telephone application with an invitation to participate in the study, after acceptance, a link to the software with the aforementioned instruments was sent. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) program using descriptive statistics, with absolute and relative frequencies, means and standard deviation; and inferential statistics, using Student's t test to analyze the difference in means. Study approved by the ethics and research committee with opinion number: 4,278,495. The results obtained with the application of the SF-36 found greater impairment in the vitality and mental health domains of adolescents who had COVID-19, compared to functional capacity and physical aspects, which presented higher averages. When linking the social determinants of health with quality of life, a statistically significant effect was observed in male adolescents with better scores in all domains of the SF-36 and in those who practiced physical activity with better scores in the general health domains. vitality and mental health. Adolescents with difficulty sleeping had worse scores in the domain of pain, general health, vitality and mental health, and those who lived with people in the risk group had worse scores in the domain of vitality and mental health. It is concluded that the social determinants of health influenced the quality of life of adolescents, and that the pandemic may have contributed to these findings, since the evaluation of the SF-36 averages found impairment in the vitality and mental health of adolescents.